Physical problems solved by the phase-integral method - Fröman, Nanny (Cambridge University Press, 2002)
Covers a mathematical approximation method of central importance to many branches of theoretical physics, applied mathematics and engineering. Written with practical needs in mind, with 50 solved problems to demonstrate the applications of the method and the concepts involved. Ideal as an introduction for graduates and a reference for researchers.